2003
DOI: 10.1086/378261
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Doubly Deuterated Hydrogen Sulfide

Abstract: This work was carried out using the Caltech Submillimeter Observatory and presents the observational study of HDS and D 2 S toward a sample of Class 0 sources and dense cores. We report the first detection of doubly deuterated hydrogen sulfide (D 2 S) in two dense cores and analyze the chemistry of these molecules, aiming to help understand the deuteration processes in the interstellar medium. The observed values of the D 2 S/HDS ratio and upper limits require an atomic D/H ratio in the accreting gas of 0.1-1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 28 publications
4
78
0
Order By: Relevance
“…Singly and doubly deuterated hydrogen sulfide have been detected in a few dark clouds Vastel et al 2003) with a significant fractionation level of ∼ 10%. The fractionation is sensitive to the temperature since HDS and D 2 S are not detected in hot cores, despite their large H 2 S column densities.…”
Section: Sulfur and Other Heavy Element Hydridesmentioning
confidence: 99%
“…Singly and doubly deuterated hydrogen sulfide have been detected in a few dark clouds Vastel et al 2003) with a significant fractionation level of ∼ 10%. The fractionation is sensitive to the temperature since HDS and D 2 S are not detected in hot cores, despite their large H 2 S column densities.…”
Section: Sulfur and Other Heavy Element Hydridesmentioning
confidence: 99%
“…Following this discovery, other doubly or triply deuterated molecules have been detected having similarly high D/H enhancements: ammonia (Roueff et al 2000;Loinard et al 2001;van der Tak et al 2002; Based on observations with the IRAM 30 m telescope in Spain and with The James Clerk Maxwell Telescope, operated by The Joint Astronomy Centre on behalf of the Particle Physics and Astronomy Research Council of the United Kingdom, the Netherlands Organisation of Scientific Research, and the National Research Council of Canada. Lis et al 2002), methanol (Parise et al 2002) and hydrogen sulfide (Vastel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a very efficient transfer of deuterium to other species (see, e.g., Roberts et al 2003, Walmsley et al 2004. This theory is supported by various observational results (Caselli et al 1999, Roueff et al 2000, Vastel et al 2003, Vastel et al 2004, Crapsi et al 2005 protonation followed by dissociative recombination reactions, but for H 2 CO recent theoretical work has shown that this route is inefficient (Osamura et al 2005). Extremely high D 2 CO/H 2 CO ratios have been observed towards both prestellar and protostellar cores and are increasingly taken to be evidence of active grain surface chemistry and desorption (e.g., Ceccarelli et al 2001, Bacmann et al 2003.…”
Section: Introductionmentioning
confidence: 78%